Herpes endotheliitis following laser-assisted in situ keratomileusis and photorefractive keratectomy - Majid Moshirfar; Melody Ziari; Christian Peterson; Neil Kelkar; Yasmyne Ronquillo; Phillip Hoopes (Taiwan Journal of Ophthalmology, 2023)
Herpes endotheliitis is a less common manifestation of herpes keratitis, and characteristic examination findings include corneal edema and the presence of keratic precipitates. Infection may be primary or secondary to herpes virus reactivation following exposure to a potential trigger such as physiologic stress or environmental factors. Ocular surgery, including laser-assisted in situ keratomileusis (LASIK) and photorefractive keratectomy (PRK), can trigger reactivation in patients with or without a documented history of previous herpes infection. We present two patients with visually insignificant stromal scarring who denied a previous history of herpetic disease and developed herpes endotheliitis following LASIK and PRK. We demonstrate the importance of an appropriately thorough preoperative evaluation and further workup of any corneal abnormalities, even if such findings initially appear inconsequential.